2021
DOI: 10.3389/fnagi.2021.742587
|View full text |Cite
|
Sign up to set email alerts
|

5 Years of Exercise Intervention Did Not Benefit Cognition Compared to the Physical Activity Guidelines in Older Adults, but Higher Cardiorespiratory Fitness Did. A Generation 100 Substudy

Abstract: Background: Aerobic exercise is proposed to attenuate cognitive decline in aging. We investigated the effect of different aerobic exercise interventions and cardiorespiratory fitness (CRF) upon cognition throughout a 5-year exercise intervention in older adults.Methods: 106 older adults (52 women, age 70-77 years) were randomized into high-intensity interval training (HIIT; ∼90% peak heart rate), moderate-intensity continuous training (MICT; ∼70% peak heart rate), or control for 5 years. The HIIT and MICT grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 98 publications
1
23
0
Order By: Relevance
“…Our findings are comparable to findings in a prospective 5-year trial, where they used a different set of cognitive tests but tested the same cognitive domains as in our study ( Sokołowski et al, 2021 ). High and moderate intensive training programmes had no effect on cognition in a dementia-free population, but there was a positive effect from high cardiorespiratory fitness at baseline.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are comparable to findings in a prospective 5-year trial, where they used a different set of cognitive tests but tested the same cognitive domains as in our study ( Sokołowski et al, 2021 ). High and moderate intensive training programmes had no effect on cognition in a dementia-free population, but there was a positive effect from high cardiorespiratory fitness at baseline.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, meta-analyses have shown that people with mild cognitive impairment have no significant increase in BDNF with exercise, even though there was a positive trend ( Ruiz-Gonzalez et al, 2021 ). In older adults without dementia, exercise programmes have also failed to show an effect on cognitive outcomes ( Sokołowski et al, 2021 ). However, those with high cardiorespiratory fitness at baseline, or those gaining high cardiorespiratory fitness, have shown improved cognitive abilities over a 5-year period ( Sokołowski et al, 2021 ), suggesting that those without dementia pathology benefits from being physically active, which in turn gives high respiratory fitness over the last 4 decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the FINGER study reported a positive effect of their multidomain intervention on processing speed in the participants with the largest structural brain reserve [29]. In our study cohort, processing speed was positively associated with VO 2peak across all participants, and increasing VO 2peak during the intervention improved working memory [30]. Taken together, this might suggest that interventions including exercise and/or physical activity provide brain functional benefits even if brain structural benefits cannot be detected.…”
Section: Discussionmentioning
confidence: 45%
“…This also shows that participants who did not reach VO 2max pushed themselves to their limit. Overall, the participants were cognitively intact and had stable cognitive abilities throughout the intervention ( Sokołowski et al, 2021 ). Over the course of the study, 2 participants died and 18 dropped out for unknown reasons.…”
Section: Resultsmentioning
confidence: 99%